A Study Into The Problems Faced By Resource Persons In The Adaptation Of Educational Technology. - Rashid Wani, Showkat; Ahmad Sheikh, Altaf; Jan Kirmani, Owaise (International Journal of Psychosocial Rehabilitation, 2020)
The emergence of Information and Communication Technology (ICT) has ushered in a new era. It has influenced every sector of the society, that is, Trade, Industry, Science and Technology including education. ICT included devices for encoding, storing, organizing, processing, retrieving, transferring and presenting information with the help of telecommunication, television and computers. The emergence of ICT is not only affecting teaching style but also influencing the learning style, whereby a student becomes the explorer of information and independent knowledge worker. The ICT has immense power to enhance personalized learning. This paper shows the opinion of Resource persons on problems faced in the implementation of educational technology during the conduct of contact classes